2014
DOI: 10.7845/kjm.2014.4057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epidemiological Characteristics, PFGE Typing and Antibiotic Resistance of Pathogenic Escherichia coli Strains Isolated from Gyeonggi-do

Abstract: This study was conducted to survey the epidemiological characteristics and the isolated strains for pathogenic E. coli which was the major causative organisms for food poisoning occurred at school food services in the Gyeonggi-do area during the past three years. We investigated 19 accidents of food-borne disease outbreaks by pathogenic E. coli at school food services from 2010 to 2012. Food-borne disease outbreaks by pathogenic E. coli were usually occurred at direct management type (18 accidents, 95%) and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, recently, it has been reported that several foodborne outbreaks, especially outbreaks of E. coli and coliform, were associated with kimchi consumption in South Korea. According to a school food service survey from 2010 to 2012, 50% of foodborne disease outbreaks occurred at schools in Gyeonggi-do Province may have been due to kimchi consumption (Kim et al, 2014). In 2012, 1642 children at seven schools in Incheon suffered from foodborne disease after eating kimchi contaminated by E. coli O169, which resulted from kimchi that had been processed after insufficient ripening periods (Cho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, it has been reported that several foodborne outbreaks, especially outbreaks of E. coli and coliform, were associated with kimchi consumption in South Korea. According to a school food service survey from 2010 to 2012, 50% of foodborne disease outbreaks occurred at schools in Gyeonggi-do Province may have been due to kimchi consumption (Kim et al, 2014). In 2012, 1642 children at seven schools in Incheon suffered from foodborne disease after eating kimchi contaminated by E. coli O169, which resulted from kimchi that had been processed after insufficient ripening periods (Cho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, kimchi has been considered to be a microbiologically safe food (Choi et al, 2018b). However, foodborne outbreaks involving kimchi from school meal services and recalls have occurred in South Korea and the United States because of foodborne pathogen contamination in kimchi, especially Listeria monocytogenes in napa cabbage (Food Safety News, 2011;NSP News Agency, 2011;KCDC, 2014;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%